Synthesis of Pd/Al2O3 coating onto a cordierite monolith and its application to nitrite reduction in water - Devard, Alejandra Veronica (2013)
The catalytic properties of Pd/Al2O3 coating onto cordierite monolith channels for the nitrite reduction in water were studied. This coating was synthesized producing an alumina layer via washcoat and adding the palladiumspecies to this layer by immersion into a PdCl2 solution.Different characterization techniques, XRD, XPS, SEMand EDXwere used to study the physicochemical andmorphological properties of the catalytic coatings. The comparison of these results alongwith the catalytic behaviors allowed comprehension of Pd active sites and theirway of acting. The structured catalyst so obtained was active and stable in the nitrite reduction.